Do teatro ao museu : a criação do Museu do Mamulengo - Espaço Tiridá - SILVA FILHO, Jorge Luiz Veloso da (2017)
This dissertation aims to understand the process of creation of the Museum of Mamulengo, in which we construct a historical narrative about the institution, highlighting the participation of its creators and partners in the composition of the collection and in the regulation of the museum. Located in the city of Olinda - PE, the Mamulengo Museum has as mission the divulgation of the theater of mamulengos, typical art of the northeastern culture. The result of the mobilization of the theater group Mamulengo Só-Riso, which in the 1970s began to acquire small collections with its own resources, on the grounds of the threat of disappearance of the popular puppet theater. The unfolding of these actions was consolidated in partnership with the Joaquim Nabuco Foundation, IPHAN, FUNARTE and the City Hall of Olinda with the inauguration of the Museu do Mamulengo - Tiridá Space in the year 1994. The methodology implemented was based on bibliographical research , Besides the documentary analysis. We used as a research source the documentation produced by the Museu do Mamulengo, as well as the documentation related to the museum in the archives of the Olinda City Hall, the National Historical and Artistic Heritage Institute and the Joaquim Nabuco Foundation. We also deal with newspaper reports that deal with the Museum and / or its agents, in addition to the numbers of Revista Mamulengo produced by the Brazilian Doll Theater Association. We conclude that the Mamulengo Museum is the result of the political mobilization of a cultural social group that articulated several institutions to build it.